The threat of systemic risk in banking: evidence for Europe - Martin Schüler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper attempts to answer the question whether the threat of systemic risk in banking exists only on a national or on a European level. Following De Nicolo and Kwast (2001), mean rolling-window correlations between bank stock returns are used as a measure for interdependencies among European banks, and hence for the systemic risk potential in Europe. National influences on stock returns are eliminated by estimating a return generating model. There is some evidence that interdependencies among European banks have increased over the past 15 years and that the potential of systemic risk has shifted from a national level to a European level.
Keywords: G21; F34; 330; systemic risk; banking; contagion; Europe; Bankenkrise; Finanzmarktkrise; Kapitalertrag; Börsenkurs; Bank; Korrelation; Schätzung; EU-Staaten; Westeuropa